Ice forces on an isolated circular pile - Frederking, R. M. W.; Gold, L. W. (1972)
This paper presents a mathematical model for calculating the forces that a moving ice cover will exert against an isolated pile. The model requires knowledge of the relationship between strain rate in the ice and the rate at which the ice cover is moving relative to the pile. An experimental and a theoretical approach to the derivation of this relationship are advanced. It is assumed that compressive failure of the ice in the zone adjacent to the pile controls the thrust on the pile. It is further assumed that the mode of failure in this zone is comparable to that for uniaxial compression tests in the laboratory. The model takes into account the influence of ice type, strain rate, pile geometry and temperature on the thrust on the pile. Le présent article propose un modèle mathématique servant à calculer les forces qu'excerce une couverture de glace en mouvement sur un pieu isolé. Le modèle exige une connaissance du rapport entre le taux de déformation dans la glace et le taux de mouvement de la couverture de glace par rapport au pieu. On présente une méthode expérimentale et une méthode théorique pour déterminer ce rapport. On suppose que la rupture de compression de la glace dans la région près du pieu contrôle la poussée contre le pieu. On suppose également que le mode de rupture dans cette région est comparable à celui qu'on retrouve dans les tests de compression uniaxiale en laboratoire. Le modèle tient compte de l'influence que le genre de glace, le taux de déformation, la géométrie du pieu et la température exercent sur la poussée contre le pieu. Peer reviewed: No NRC publication: Yes